FORMULASI DAN UJI STABILITAS FISIK LULUR TRADISIONAL AMPAS KOPI (Coffea sp.) DAN BUAH GAMBAS (Luffa Acutangula L.) - Maemunah, Salsa Nabila; Riyanta, Aldi Budi; Amananti, Wilda (Jurnal Insan Cendekia, 2025)
Introduction: Coffee grounds and gambas fruit have the potential to be used as preparations for making traditional body scrubs. Coffee grounds contain caffeine that can tighten blood vessels, while gambas fruit is rich in antioxidants that can cleanse and brighten the skin. Objective: This study aims to determine the stability of traditional body scrubs made from coffee grounds and luffa fruit that meet the requirements. Method : The luffa fruit used comes from Pemalang Morning Market. The luffa fruit preparation method with a drying process using direct sunlight is continued with a grinding and sieving process using mesh 44. Coffee grounds powder is obtained from the Az-Zakhra shop then the grinding process is carried out using a blender and sieving using mesh 44. Results: Next, the stability test process was carried out with storage for 4 weeks with physical tests every week, the physical tests that were tested were organoleptic tests, homogeneity tests, pH tests, spreadability tests, and adhesion tests. The physical properties of the scrub test included organoleptic tests, homogeneity tests, pH tests, which were produced to meet the standards, while in the spreadability and adhesion tests there were formulas that did not meet the standards. Storage of the scrub preparation at room temperature until the 4th week. Conclusion: Based on the physical stability test, formula I and formula II are formulas that meet the physical stability test standards, the stability test shows that storing the scrub from week 0 to week 4 does not affect the preparation.